2021
DOI: 10.3389/fcell.2021.666484
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary Conserved Transmembrane BAX Inhibitor Motif (TMBIM) Containing Protein Family Members 5 and 6 Are Essential for the Development and Survival of Drosophila melanogaster

Abstract: The mammalian Transmembrane BAX Inhibitor Motif (TMBIM) protein family consists of six evolutionarily conserved hydrophobic proteins that affect programmed cell death and the regulation of intracellular calcium levels. The bacterial ortholog BsYetJ is a pH-dependent calcium channel. We here identified seven TMBIM family members in Drosophila melanogaster and describe their expression levels in diverse tissues and developmental stages. A phylogenetic analysis revealed that CG30379 represents the ortholog of hum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
2
1
0
Order By: Relevance
“…Absence of TMBIM5 protein was confirmed by immunoblotting ( Fig 2A ). TMBIM5 -deficient cells have a disrupted cristae architecture with loss of cristae ( Fig 2B ) and reduced maximal uncoupled mitochondrial respiration as shown by a Seahorse analysis ( Fig 2C ) similar to previously reported TMBIM5 loss-of-function cellular phenotypes ( Oka et al, 2008 ; Seitaj et al, 2020 ; Zhang et al, 2021 ). Based on these findings, we concluded that our TMBIM5 KO HEK293 cells constitute a bona fide model to study the effects of TMBIM5 loss of function on mitochondrial Ca 2+ dynamics.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Absence of TMBIM5 protein was confirmed by immunoblotting ( Fig 2A ). TMBIM5 -deficient cells have a disrupted cristae architecture with loss of cristae ( Fig 2B ) and reduced maximal uncoupled mitochondrial respiration as shown by a Seahorse analysis ( Fig 2C ) similar to previously reported TMBIM5 loss-of-function cellular phenotypes ( Oka et al, 2008 ; Seitaj et al, 2020 ; Zhang et al, 2021 ). Based on these findings, we concluded that our TMBIM5 KO HEK293 cells constitute a bona fide model to study the effects of TMBIM5 loss of function on mitochondrial Ca 2+ dynamics.…”
Section: Resultssupporting
confidence: 86%
“…To study the endogenous function of TMBIM5, we generated TMBIM5-deficient HEK293 cells using CRISPR/Cas9. Absence of TMBIM5 protein was confirmed by immunoblotting (Fig 2A (Oka et al, 2008;Seitaj et al, 2020;Zhang et al, 2021). Based on these findings, we concluded that our TMBIM5 KO HEK293 cells constitute a bona fide model to study the effects of TMBIM5 loss of function on mitochondrial Ca 2+ dynamics.…”
Section: No Alteration Of Mitochondrial Ca 2+ Uptake In Tmbim5-defici...supporting
confidence: 56%
See 1 more Smart Citation